2006
DOI: 10.1134/s0006297906020064
|View full text |Cite|
|
Sign up to set email alerts
|

A false note of DNA polymerase iota in the choir of genome caretakers in mammals

Abstract: DNA polymerase iota (Pol iota) of mammals is a member of the Y family of DNA polymerases. Among many other genome caretakers, these enzymes are responsible for maintaining genome stability. The members of the Y-family DNA polymerases take part in translesion DNA synthesis, bypassing some DNA lesions, and are characterized by low fidelity of DNA synthesis. A unique ability of Pol iota to predominantly incorporate G opposite T allowed us to identify the product of this enzyme among those synthesized by other DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Indeed, no pol protein was detected by Western blotting of testis extracts of 129 mice using an antibody raised against the COOH terminus of murine pol that recognizes full-length or misspliced variants of pol (26). However, a recent study (48) has reported that crude extracts of brain cells from 129͞J mice (but not extracts of other 129͞J cells) have the ability to insert dGMP opposite template T in an oligonucleotide primer template. The authors claim this misinsertion activity is due to pol rather than any of the other DNA polymerases that can insert dGMP opposite T, and they further speculate that brain cells of 129 mice contain alternatively spliced pol that retains catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, no pol protein was detected by Western blotting of testis extracts of 129 mice using an antibody raised against the COOH terminus of murine pol that recognizes full-length or misspliced variants of pol (26). However, a recent study (48) has reported that crude extracts of brain cells from 129͞J mice (but not extracts of other 129͞J cells) have the ability to insert dGMP opposite template T in an oligonucleotide primer template. The authors claim this misinsertion activity is due to pol rather than any of the other DNA polymerases that can insert dGMP opposite T, and they further speculate that brain cells of 129 mice contain alternatively spliced pol that retains catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, on the basis of an analytical assay designed to detect the unique mutagenic profile of Pol, Gening and colleagues (16) showed that in 129/J strain mice, Pol activity was detectable in brain extracts but not in testis. In this report, we provide extensive evidence showing that 129-derived strains are indeed not completely deficient in Pol but rather express a variant of the Pol protein that retains catalytic activity in a wide variety of tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The 129-derived 129/SvJ and 129/Ola mouse strains possess a nonsense mutation in codon 27 of exon 2 in both alleles and have been reported to be naturally deficient in Pol (15). However, data from Gening and colleagues determined using a specific Pol activity assay suggested the presence of residual activity in brain extracts of 129-derived mouse strains (16).…”
mentioning
confidence: 93%
“…The cell extracts were prepared as previously described (Gening et al 2006;Kazakov et al 2008). The three complementary oligonucleotides (the 17 nt universal primer and two 30 mer templates) were gel purified and used to test ''misGvA'' activity.…”
Section: Assay Of Dna Polymerase Activity In Cell Extractsmentioning
confidence: 99%
“…Therefore, the search for new methods and models for analysis of expression, biochemical properties, functions, and regulation of Pol i is urgent. As a step to understanding the in vivo functions of Pol i, we recently proposed a method of determination of Pol i activity in crude cell extracts of animal tissues and human tumors which was based on the detection of Pol i-specific ''misGvA'' activity (Gening et al 2006;Kazakov et al 2008). We further increased the sensitivity of the assay by replacing Mg 2?…”
Section: Introductionmentioning
confidence: 99%